Activated Mast Cells Combined with NRF2 Predict Prognosis for Esophageal Cancer. (4th January 2023) - Guo, Xinxin; Shen, Weitao; Sun, Mingjun; Lv, Junjie; Liu, Ran
Abstract : Background . Esophageal cancer (EC) had the sixth-highest mortality rate of all cancers due to its poor prognosis. Immune cells and mutation genes influenced the prognosis of EC, but their combined effect on predicting EC prognosis was unknown. In this study, we comprehensively analyzed the immune cell infiltration (ICI) and mutation genes and their combined effects for predicting prognosis in EC. Methods . The CIBERSORT and ESTIMATE algorithms were used to analyse the ICI scape based on the TCGA and GEO databases. EC tissues and pathologic sections from Huai'an, China, were used to verify the key immune cells and mutation genes and their interactions. Results . Stromal/immune score patterns and ICI/gene had no statistical significance in overall survival (OS) (p > 0.05 ). The combination of ICI and tumor mutation burden (TMB) showed that the high TMB and high ICI score group had the shortest OS (p = 0.004 ). We recognized that the key mutation gene NRF2 was significantly different in the high/low ICI score subgroups (p = 0.002 ) and positivity with mast cells (MCs) (p < 0.05 ). Through experimental validation, we found that the MCs and activated mast cells (AC-MCs) were more infiltration in stage II/III (p = 0.032 ; p = 0.013 ) of EC patients and that NRF2 expression was upregulated in EC (p = 0.045 ). AC-MCs combined with NRF2 had a poor prognosis, according to survival analysis (p = 0.056 ) and interactive analysis (p = 0.032 ). Conclusions . We presume that NRF2 combined with AC-MCs could be a marker to predict prognosis and could influence immunotherapy through regulating PD-L1 in the EC.